2022
DOI: 10.1128/aac.00936-22
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ceftazidime-Avibactam in Combination with Aztreonam (COMBINE) in a Phase 1, Open-Label Study of Healthy Adults

Abstract: Scant pharmacokinetic (PK) data are available on ceftazidime-avibactam (CZA) and aztreonam (ATM) in combination, and it is unknown if CZA-ATM exacerbates alanine aminotransferase (ALT)/aspartate aminotransferase (AST) elevations relative to ATM alone. This phase 1 study sought to describe the PK of CZA-ATM and assess the associations between ATM exposures and ALT/AST elevations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Also, without loading doses, there will be on average a longer time to achieve targets in the critical early phase of treatment. In addition, the safety (including transaminase liability) of ceftazidime-avibactam plus aztreonam is unknown, although transaminase elevations have been reported to be more frequent with combinations including 8 g/day of aztreonam compared to those including 6 g/day [47]. Overall, the 'off-label' use of combinations of ceftazidime-avibactam plus aztreonam might not provide adequate exposures for all patients across the range of pathogen susceptibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Also, without loading doses, there will be on average a longer time to achieve targets in the critical early phase of treatment. In addition, the safety (including transaminase liability) of ceftazidime-avibactam plus aztreonam is unknown, although transaminase elevations have been reported to be more frequent with combinations including 8 g/day of aztreonam compared to those including 6 g/day [47]. Overall, the 'off-label' use of combinations of ceftazidime-avibactam plus aztreonam might not provide adequate exposures for all patients across the range of pathogen susceptibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Aztreonam, co-administered with CAZ/AVI, was studied in healthy subjects which resulted in reduced AZT clearance. Meanwhile, continuously infused AZT was associated with severe hepatic transaminase elevations [ 113 ].…”
Section: Antimicrobials In Phase 3 Clinical Trialsmentioning
confidence: 99%
“…Although hepatic aminotransferase elevations were observed in 40% of the volunteers, none had any clinical findings suggestive of acute liver failure. Furthermore, the results of the PK analyses revealed that ATM clearance may be reduced when it is used in combination with CZA, thus resulting in higher-than-anticipated plasma exposure profiles in patients with reduced renal function and possibly more exposure-related adverse effects [130 ▪ ]. Finally, limited but promising clinical data suggests that CZA-ATM may be used for Sma infections [84 ▪ ,131,132].…”
Section: Introductionmentioning
confidence: 99%